Personalized nursing as the missing link of providing care: A systematic review - Mohammadamin Jandaghian-Bidgoli; Sheida Jamalnia; Marzieh Pashmforosh; Negin Shaterian; Pouriya Darabiyan; Alireza Rafi (BMC Nursing)
Abstract This study aimed to evaluate the efficacy of personalized nursing care. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we systematically searched multiple databases and search engines, including PubMed, Scopus, ProQuest, CINAHL, and Google Scholar, for articles published between 2011 and September 31, 2022. To evaluate the quality of the incorporated studies, we utilized established assessment tools, including the CONSORT checklist, STROBE statement, and Kmet standard criteria. A qualitative narrative synthesis approach was employed for data synthesis. The systematic review included 24 studies involving 5428 participants. Across these studies, a consistent positive correlation was found between personalized care administered by nurses and participant satisfaction. Patients receiving personalized care experienced reduced negative emotional symptoms, suggesting potential therapeutic benefits extending beyond physical health outcomes. Health guidance education, individualized healthcare plan and dedicated nursing team were the examples of personalized nursing interventions. The results underlined the importance of personalized nursing in delivering essential services. Personalized nursing aims to improve the quality of care by adapting it to each individual’s unique needs and characteristics. Patient or public contribution: This study did not include contributions from patients or the public. Systematic Review Registration: CRD42022367814.